Problematizing Fertility: A Policy Analysis of Latvia’s Demographic Strategy - Dance,Ance (2025)
With Latvia being one of the many countries in the world experiencing low fertility rates and having a below-replacement-level birth rate for decades, fertility decline has become a central concern for policymakers. This thesis examines how low fertility is framed and addressed in Latvian demographic policy documents. By using an inductive, qualitative case study approach and utilizing Carol Bacchi’s “What’s the Problem Represented to Be” approach for policy analysis, this study explores how the issue of depopulation is problematized, what assumptions exist behind the problem representations, and what is left unproblematized. The Second Demographic Transition Theory and Gender Equality are used as the theoretical frameworks guiding the research. The thesis finds that demographic decline is problematized as the overarching issue that is impacted by and causes several other factors. The causes include delayed parenthood, changing family values, “non-traditional” households, gender equality, and high divorce rates. The consequences are found to be the loss of human capital, access to resources, an ageing population, and the availability of state support. The assumptions are identified as being concerned with the preference for an ideal family type and how the state views its citizens. Finally, the unproblematized aspects are associated with environmental considerations and policy planning contradictions.
Keywords: fertility; depopulation; family; policy; Latvia; WPR approach